Hubungan Antara Media Sosial dengan Kunjungan Pasien di Rumah Sakit: A Scoping Review - Fawzia Haura Fathin; Zahroh Shaluhiyah (Universitas Malahayati Lampung, 2026)
ABSTRACT Social media platforms enable rapid information dissemination and direct communication with patients and communities worldwide. This encourages healthcare providers to integrate them for health promotion, brand building, and professional networking. The objective of this research is to conduct a comprehensive review of the scholarly works concerning leveraging social media for enhancing hospital patient traffic. This scoping review utilized data from EBSCO host, Oxford, PubMed, and Scopus. The inclusion criteria were publications from the last eight years, available in full-text, open access, English-language, and of the article document type. The keywords used combined terms for social media (e.g.,